Verification measurements of an eMC algorithm using a 2D ion chamber array - Wanklyn, Mark D. (J Appl Clin Med Phys, 2016)
The aim of this study was to assess the suitability of the Im'RT MatriXX 2D ion chamber array for performing verification measurements on the Varian Eclipse electron Monte Carlo (eMC) algorithm for a range of clinical energies (6, 12, and 20 MeV) on a Varian 2100iX linear accelerator. Firstly, the suitability of the MatriXX for measuring percentage depth doses (PDD) in water was assessed, including characterization of the inherent buildup found in the MatriXX. Secondly the suitability of the MatriXX for measuring dose distributions in homogeneous and heterogeneous phantoms was assessed using gamma analysis at [Formula: see text]. It was found that after adjusting the PDD curves for the inherent buildup, that the position of [Formula: see text] measured using the MatriXX agreed to within 1 mm to the PDDs generated using the eMC algorithm for all energies used in this study. Gamma analysis at [Formula: see text] showed very good agreement ([Formula: see text]) for all cases in both homogeneous and heterogeneous phantoms. It was concluded that the Im'RT MatriXX is a suitable device for performing eMC verification and could potentially be used for routine energy checks of electron beams. PACS number(s): 87.55.km, 87.55.Qr